Chitosan composites synthesized using acetic acid and tetraethylorthosilicate respond differently to methylene blue adsorption - Essel, T.Y.A.; Koomson, A.; Seniagya, M.O.; Cobbold, G.P.; Kwofie, S.K.; Asimeng, B.O.; Arthur, P.K.; Awandare, G.; Tiburu, E.K. (Polymers, 2018)
The sol-gel and cross-linking processes have been used by researchers to synthesize silica-based nanostructures and optimize their size and morphology by changing either the material or the synthesis conditions. However, the influence of the silica nanostructures on the overall physicochemical and mechanistic properties of organic biopolymers such as chitosan has received limited attention. The present study used a one-step synthetic method to obtain chitosan composites to monitor the uptake and release of a basic cationic dye (methylene blue) at two different pH values. Firstly, the composites were synthesized and characterized by Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD) to ascertain their chemical identity. Adsorption studies were conducted using methylene blue and these studies revealed that Acetic Acid-Chitosan (AA-CHI), Tetraethylorthosilicate-Chitosan (TEOS-CHI), Acetic Acid-Tetraethylorthosilicate-Chitosan (AA-TEOS-CHI), and Acetic Acid-Chitosan-Tetraethylorthosilicate (AA-CHI-TEOS) had comparatively lower percentage adsorbances in acidic media after 40 h, with AA-CHI adsorbing most of the methylene blue dye. In contrast, these materials recorded higher percentage adsorbances of methylene blue in the basic media. The release profiles of these composites were fitted with an exponential model. The R-squared values obtained indicated that the AA-CHI at pH ~2.6 and AA-TEOS-CHI at pH ~7.2 of methylene blue had steady and consistent release profiles. The release mechanisms were analyzed using Korsmeyer-Peppas and Hixson-Crowell models. It was deduced that the release profiles of the majority of the synthesized chitosan beads were influenced by the conformational or surface area changes of the methylene blue. This was justified by the higher correlation coefficient or Pearson's R values (R ≥ 0.5) computed from the Hixson-Crowell model. The results from this study showed that two of the novel materials comprising acetic acid-chitosan and a combination of equimolar ratios of acetic acid-TEOS-chitosan could be useful pH-sensitive probes for various biomedical applications, whereas the other materials involving the two-step synthesis could be found useful in environmental remediation of toxic materials. © 2018 by the authors.
Keywords: Chitosan; Cross-linking; FTIR; Interpenetrating; Methylene blue; Modelling; TEOS; XRD